Gender-Specific Application Behaviour, Matching, and the Residual Gender Earnings Gap - Benjamin Lochner; Christian Merkl (Global Labor Organization (GLO), 2025)
This paper examines how gender-specific application behaviour, firms' hiring practices, and flexibility demands relate to the gender earnings gap, using linked data from the German Job Vacancy Survey and administrative records. Women are less likely than men to apply to high-wage firms with high flexibility requirements, although their hiring chances are similar when they do. We show that compensating differentials for firms' flexibility demands help explain the residual gender earnings gap. Among women, mothers experience the largest earnings penalties relative to men in jobs with high flexibility requirements.
Keywords: E24; J16; J31; 330; Job Search; Application Behaviour; Gender Earnings Gap